Factors Influencing KAM Reporting: A Structured Literature Review - Teodora PORUMBACEAN (Chamber of Financial Auditors of Romania, 2021)
The disclosure of KAMs contribute to the increase of financial-reporting quality, the value of the audit report and implicit interest in it. Moreover, KAM’s disclosure has a positive influence over the expectation gap between the auditors and other users of the audit report and financial statements. This study aims to identify relevant drivers influencing the Key Audit Matters (KAMs) disclosed in the audit report, based on a review of the articles published in top accounting journals. Our results reveal the fact that the audited company itself especially influences the disclosure of the KAMs, emphasizing the size of the company, the complexity of the business, the applicable regulation of the industry in which the company operates, all of which impact the overall client-risk level. Other relevant factors are the accounting standards with which the company must comply and on which it must report, the audit company (‘Big Four’ or not) and the audited company’s location.